POPULATION OF Osteochllus spp. AS A BASE OF SUSTAINABLE FISHING IN SERAYU RIVER - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The increasingdemand for fresh water resources generatedbyhuman population growth, urbanization, industrialization and irrigationhave resultedina declineor loss offreshwaterfishsuch as Osteochilus spp. The aims of research were to analysisthe populationof Osteochilusspp Interms of abundance, longitudinaldistributionand sex ratio and to determine environmentalfactors of river driventhese populations.The research was carriedout at upper part of Serayu Riverduringwet season (January - March) and dry season (June -August) 2007. Fishes were collected by using electro fishing and stratified random sampling was applied by dividing this river Into five strata based on altitude. The results showed that the total abundances of Osteochilus spp. was 149 individuals and composed by O. hasselti (47) with 8.30 - 24.35 em and 11.20 - 198.70 g, O. microchephalus (101) with 11.35 - 25.21 em and 17.9 - 206.5 g and O.kahajanensis (1) with 17.30 em and 68.80 g. The size of population O. hasselti and O. microchephalus gradually increased from 7 and 4 individuals in stratum A became 27 and 12 individuals In stratum D, and then increased up to 43 and 17 individuals in stratum E. The sex ratio of O. hasseltiwas 10:16 and O. microchephalus was 20:23. Both species were longitudinally distributed In Serayu River. It seems that the population of O. hasellti and O. microchephalus were more influenced by physical factors such as depth and current rather than chemical factors i.e. DO and pH at Serayu River.